1993
DOI: 10.1016/0035-9203(93)90501-g
|View full text |Cite
|
Sign up to set email alerts
|

Lytic antibody titre as a means of assessing cure after treatment of Chagas disease: a 10 years follow-up study

Abstract: A complement-mediated lysis test (CoML) using living trypomastigotes was compared with conventional serological methods and with haemoculture. Over a 10 years follow-up period evidence was obtained which supported the view that chagasic patients, treated with nitroheterocyclic drugs, in whom CoML had reverted to negative, might be considered cured despite conventional serology remaining positive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
127
1
2

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(137 citation statements)
references
References 10 publications
5
127
1
2
Order By: Relevance
“…The CoML test has been a useful tool in establishing the existence of an active ongoing infection. After specific treatment some patients are regularly negative in CoML assays but only as small percentage of treated patients present negative results in conventional serology antibodies (CSA) detection (Galvao et al, 1993;Sánchez et al, 1995;Zulantay et al, 2004). In considering the technical laboriousness of CoML, Martins-Filho (2002) proposed an alternative tool (FC-ALTA) that was demonstrated to be comparable to CoML for monitoring the treatment effectiveness in cases of human Chagas disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CoML test has been a useful tool in establishing the existence of an active ongoing infection. After specific treatment some patients are regularly negative in CoML assays but only as small percentage of treated patients present negative results in conventional serology antibodies (CSA) detection (Galvao et al, 1993;Sánchez et al, 1995;Zulantay et al, 2004). In considering the technical laboriousness of CoML, Martins-Filho (2002) proposed an alternative tool (FC-ALTA) that was demonstrated to be comparable to CoML for monitoring the treatment effectiveness in cases of human Chagas disease.…”
Section: Discussionmentioning
confidence: 99%
“…It has always been difficult to evaluate the incidence of cure in chronic chagasic patients who have received anti-parasitic treatment by serology, since a humoral response against T. cruzi antigens may remain for years even in the absence of the parasite (Galvao et al, 1993). Antibodies present in the serum of chagasic patients induce lysis in trypomastigote forms in the presence of complement (CoML), indicating the presence of active infection (Galvao et al, 1993;Sánchez et al, 1995). Following specific treatment, lytic antibodies disappear from the serum of some patients while conventional serology remains positive.…”
mentioning
confidence: 99%
“…Such type of infections contrast with natural parasitism by T. cruzi, which results from low numbers of vector-borne parasites penetrating epithelia and which require more sensitive methods for detection. Only 14 of the 66 studies included methods of higher sensitivity than fresh blood mount (e.g., xenodiagnosis, hemoculture and sub-inoculation) and none of them used serological methods to exclude infection, as practiced by clinicians on patients (Galvão et al 1993). Two of these studies deserve a special comment in this context, because both used the CML technique and, in one of them, parasitological results suggest total protection.…”
Section: Discussionmentioning
confidence: 99%
“…Lytic antibodies are important immunologic effectors, associated with active infection and resistance against this parasite . The absence of lytic antibodies is considered to be indicative of cure, in spite of positive findings with other, so called, conventional serological tests , Galvão et al 1993.…”
mentioning
confidence: 99%
“…The existence of lytic antibodies had been considered as an indicator of active infection and its absence after chemotherapeutic treatment would indicate cure (Brener & Krettli, 1990). Drugs (Rochagan 1 , Radanil 1 , Lampit 2 ) utilized in the last decades for antichagasic treatment are potentialy toxic compounds that present diverse secondary manifestations and they are only recommended for acute cases since they play a limited role in the specific treatment of chronic cases (Apt et al, 1986 ;Galvao et al, 1993 Itraconazole, a synthetic imidazole, was shown to be highly effective against T. cruzi both in vivo and in vitro experiments (McCabe et al, 1986). In the present study the efficacy of itraconazole on chronic chagasic patients is evaluated by means of xenodiagnosis, conventional serology and lytic antibodies detection.…”
Section: Introductionmentioning
confidence: 99%